Spectral emission analysis of a dc helium hollow cathode discharge - Chin, Oi Hoong; Wong, C.S. (2003)
A fully developed hollow cathode discharge in which the negative glows from opposite walls coalesce to form full column is observed from the measured radial profile of the spectral line emission intensity from within the cathode space. The occurrence of this fully developed hollow cathode discharge is found to depend on the pressure of the working gas p, the discharge current IA and the hollow cathode configuration. The results obtained agrees with those deduced from the optimum pressure range defined in the VA versus p (IA fixed) curves. HeI triplet and singlet lines are detected under most of the discharge conditions and hollow cathode configuration investigated but the singly charged ionic line HeII 468.57 nm is detected only at conditions under which the fully developed hollow cathode discharge is defined. The radial distribution of the ionic HeII line emission is indicative of the radial distribution of the high energy (~10Â² eV, close to the cathode fall potential) electron densities and is observed to peak at the axis. The total intensities of the HeI emission lines are found to be proportional to IA(0.8-1.2) while that of the ionic HeII emission line is proportional to IA3.3. The width of the cathode dark space is deduced from the radial distribution profiles of the emission lines. From these, the average reduced electric field in the cathode dark space is also estimated.